REPRESENTASI KEKERASAN SEKSUAL PADA PEREMPUAN: Studi Analisis Semiotika dalam Film â€œ7 Hati 7 Cinta 7 Wanitaâ€ - Valerina, Wisti (JURNAL KOMUNITAS, 2013)
The globalization implies the existence of an infinite information. Furthermore, the audience themselves to be smart in choosing and receive information on get it. One of medium is film. Various types of films that update will become a factor in the audience to absorb the information that is in the vicinity. Information about sexual violence on women, for example, will always be a hot topic discussed due to rampant cases of sexual violence involving women as victims. This study aims to determine the sexual assault case that represented in the film â€œ7 Hati 7 Cinta 7 Wanitaâ€. This case may be existing in our neighbourhood. This film gives taught to women, especially Indonesian women not to dissolve into the feelings and in the end only be a mere victim. This research is a qualitative study using semiotic analysis. Research shows that film â€œ7 Hati 7 Cinta 7 Wanitaâ€ has five elements of sexual violence on women by the National Commission on Violence Against Women (Komnas Perempuan) which is probably the result representation of what is around us. Five elements are: (1 ) Sexual Harassment, (2) Sexual Torture, (3) Abortion Coercion, (4) Forced Marriage, and (5) Trafficking of Women for Sexual Purposes. The five elements, perhaps even to the 15 elements of sexual violence on women already in the grade by the National Commission for Women are there around us.